Investment Strategies for Capital Market Participation Among Generasi Z: Strategi Investasi untuk Partisipasi Generasi Z di Pasar Modal - Anggraini, Julina; Hanif, Aisha (Indonesian Journal of Law and Economics Review, 2024)
Background: Understanding the decision-making process of investors is vital in the evolving capital market, especially among Generation Z. Specific Background: This generation encounters unique challenges and opportunities as they define their financial goals. Knowledge Gap: Limited research exists on the specific factors influencing Generation Z’s investment decisions. Aims: This study investigates the motivators behind Generation Z's choices in the capital market using a qualitative phenomenological approach. Results: Findings identify key influences such as investment knowledge, income, risk tolerance, and return expectations, demonstrating that financial literacy significantly impacts decision-making. Novelty: This research highlights the need for targeted financial education resources for Generation Z. Implications: The study emphasizes the importance of tailored financial education programs to enhance informed participation in the capital market. Highlights : Investment decisions are influenced by financial literacy and knowledge. Income levels and risk tolerance shape investment choices among Generation Z. Tailored financial education is essential for informed market participation. Keywords:Generation Z, Investment, Knowledge, Risk, Decision-making